El equinodermo Gogia granulosa (Echinodermata: Blastozoa) del Cámbrico temprano-medio en Sonora, México: paleoecología y paleogeografía - Buitrón Sánchez, Blanca E.; Cuen Romero, Francisco J.; Montijo González, Alejandra; Beresi, Sylvia Matilde (Revista de Biología Tropical, 2017)
The echinoderm Gogia granulosa (Echinodermata: Blastozoa) of early-mid Cambrian in Sonora, Mexico: paleoecology and paleogeography. Blastoids of Gogia granulosa Robison, 1965 and Gogia sp. have previously been reported from San Jose de Gracia, Sonora, Mexico. Here we report on the implications of their presence in limestone, shale, and sandstone from the lower-middle Cambrian of that site. The biotic association consists of blastoids, as well as trilobites (Onchocephalus, Bonnia, Bristolia, Olenellus), hyolithids (Hyolithes, Haplophrentis), sponges, algae and ichnofossils of echinoderms (Asteriacites, Asterosoma). The community suggests that the depositional environment was a carbonated platform of tropical, shallow sea, with well oxygenated water. The biota belonged to a large faunistic province that comprised parts of Canada, USA and Mexico (Panthalassic Ocean). Rev. Biol. Trop. 65(Suppl. 1): S160-S167. Epub 2017 November 01.